The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10327-008-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lodging on the level of mycotoxins in wheat, barley, and rice infected with the Fusarium graminearum species complex

Abstract: Lodging is one possible risk factor that leads to increased cereal mycotoxin contamination, but few reports have been published on the subject. We examined the effects of lodging on the level of deoxynivalenol (DON) and nivalenol (NIV) contamination in wheat, barley, and rice infected with the Fusarium graminearum species complex. Case-control and intervention studies were applied to test the hypothesis that lodging increases the level of mycotoxin contamination. A total of 66 grain samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…In a previous study, relatively high N rates were also shown to increase lodging in barley (Spaner et al, 2001). Lodging can adversely aff ect barley yield and quality (Jedel and Helm, 1991)) and increase mycotoxin contamination (Nakajima et al, 2008).…”
Section: Effect Of Nitrogen Ratementioning
confidence: 86%
“…In a previous study, relatively high N rates were also shown to increase lodging in barley (Spaner et al, 2001). Lodging can adversely aff ect barley yield and quality (Jedel and Helm, 1991)) and increase mycotoxin contamination (Nakajima et al, 2008).…”
Section: Effect Of Nitrogen Ratementioning
confidence: 86%
“…Although none of these species were abundant in the study plot, their presence could be used to establish guidelines for good agricultural practices to minimize the risks of mycotoxin contamination of cereal products (Nakajima et al 2008). Interest in this genus is increasing worldwide due to the discovery of a growing number of naturallyoccuring Fusarium toxins that have proved to be a threat to human and animal health (Kharunakara Murthy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are also consistent with results of Bernhoft et al (2012), who reported that F. langsethiae was less frequent in lodged fields. Bernhoft et al (2012) also reported that lodged fields were connected to increased infestation by F. graminearum, and Nakajima et al (2008) observed the formation of abundant perithecia on the spikes of lodged wheat at harvest. However, in our experiment, the high content of DON in 'Bogatka's grain in 2010 was not accompanied with high percentage of 'Bogatka's kernels infected by F. graminearum.…”
Section: Contents Of Fusarium Toxinsmentioning
confidence: 92%
“…Moreover, analysis of variance showed that DON and ZEA content in the Bernhoft et al (2012) reported that low temperature before harvest was the factor found to increase DON concentration in wheat grain. Also Nakajima et al (2008) found that lodging had a significant increasing effect on DON and nivalenol content in wheat grain. Our data are also consistent with results of Bernhoft et al (2012), who reported that F. langsethiae was less frequent in lodged fields.…”
Section: Contents Of Fusarium Toxinsmentioning
confidence: 97%